2021
DOI: 10.1017/s0950268821000054
|View full text |Cite
|
Sign up to set email alerts
|

Who is dying from COVID-19 in the United Kingdom? A review of cremation authorisations from a single South Wales' crematorium

Abstract: Only studies in the UK on individuals dying from coronavirus disease 2019 (COVID-19) in hospital have been published, to date. Cremation law requires collection of clinical information that can improve understanding of deaths in both hospital and community settings. Age, sex, date and place of death, occupation, comorbidities and where infection acquired was recorded for all deaths from COVID-19, between 6 April and 30 May, for whom an application was made for cremation at a South Wales' crematorium. Of 752 cr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…It is also important to appreciate that as studies typically reported all-cause mortalityand information on age, frailty, and co-morbidities were not available at the individual patient level -the causal contribution of nosocomial COVID-19 exposure remains to be determined. Examination of linked primary care and mortality data within the United Kingdom (62,63) suggests that COVID-19 amplifies the risk of death by a factor associated with the levels of circulating virus and an individuals' underlying diagnoses (62). Shah et al describe how active SARS-CoV-2 infection often led to decisions to forgo anticancer treatment in hospitalised patients with haematological malignancies (51).…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to appreciate that as studies typically reported all-cause mortalityand information on age, frailty, and co-morbidities were not available at the individual patient level -the causal contribution of nosocomial COVID-19 exposure remains to be determined. Examination of linked primary care and mortality data within the United Kingdom (62,63) suggests that COVID-19 amplifies the risk of death by a factor associated with the levels of circulating virus and an individuals' underlying diagnoses (62). Shah et al describe how active SARS-CoV-2 infection often led to decisions to forgo anticancer treatment in hospitalised patients with haematological malignancies (51).…”
Section: Discussionmentioning
confidence: 99%